2022
DOI: 10.3389/fcimb.2022.1003033
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to prevent, curb and eliminate biofilm formation based on the characteristics of various periods in one biofilm life cycle

Abstract: Biofilms are colonies of bacteria embedded inside a complicated self-generating intercellular. The formation and scatter of a biofilm is an extremely complex and progressive process in constant cycles. Once formed, it can protect the inside bacteria to exist and reproduce under hostile conditions by establishing tolerance and resistance to antibiotics as well as immunological responses. In this article, we reviewed a series of innovative studies focused on inhibiting the development of biofilm and summarized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 174 publications
0
12
0
Order By: Relevance
“…Furthermore, TFBZ interfered with the expression of translation initiation factor- infC and ribosomal protein -rplN , attributing to impediment of key proteins synthesis required for microbial growth and biofilm formation ( Korostelev et al, 2010 ). Additionally, downregulation of murQ and dltB genes hindered the biosynthesis of peptidoglycan precursors and affected the remodeling of the cell wall, reducing the resistance of MRSA biofilms toward the host immune system and antibiotics ( Wood et al, 2018 ; Ma et al, 2022 ). Since MoeA protein is essential for production of active molybdoenzymes, TFBZ might perturb the assemble of molybdenum cofactor into the molybdoenzymes, leading to the metabolism disorder of nitrate reduction and sulfur compound conversion in MRSA ( Hasona et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TFBZ interfered with the expression of translation initiation factor- infC and ribosomal protein -rplN , attributing to impediment of key proteins synthesis required for microbial growth and biofilm formation ( Korostelev et al, 2010 ). Additionally, downregulation of murQ and dltB genes hindered the biosynthesis of peptidoglycan precursors and affected the remodeling of the cell wall, reducing the resistance of MRSA biofilms toward the host immune system and antibiotics ( Wood et al, 2018 ; Ma et al, 2022 ). Since MoeA protein is essential for production of active molybdoenzymes, TFBZ might perturb the assemble of molybdenum cofactor into the molybdoenzymes, leading to the metabolism disorder of nitrate reduction and sulfur compound conversion in MRSA ( Hasona et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both methods of increasing the antibiotic load produced related results, which shows that the antibiotic dose can be controlled through layering whilst retaining good efficacy against the planktonic cells. The prevention of planktonic cell attachment is important as they instigate the initial adhesion onto the surface that leads to the micro colony [ 30 ]. These initial stages after implantation are extremely important as the host immune system is weakened [ 31 ] and can allow a microbe to win the race to the surface [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Planktonic bacteria are unstable and are easy to eliminate. Therefore, repelling bacteria during reversible adhesion is an efficient and economical strategy to prevent biofilm formation . Once irreversible adhesion begins, stronger physical or chemical forces are required to remove the bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, repelling bacteria during reversible adhesion is an efficient and economical strategy to prevent biofilm formation. 13 Once irreversible adhesion begins, stronger physical or chemical forces are required to remove the bacteria. 5 In recent years, researchers have found that microorganisms can distinguish different stereochemical structures (such as chirality) and regulate their reversible adhesion in the microbe−surface interaction.…”
Section: Introductionmentioning
confidence: 99%